Lost and found website development - Chen, Kit Yeng (2020)
The title of this project is called “Lost and Found Website”. This website is to let users to search for missing people cases in the Malaysia through online platform. Based on the report provided by police, approximately 2000 people went missing per year in Malaysia. However, many Malaysian still lack of awareness in the lost people cases because the relevant website is very limited. Hence, the main objective of this project is to develop a website that is able to gather information of the missing people. By gathering all the information through the website, user can easily search for the information and able to update the latest missing cases that happen around the community. Besides that, implementation of data collection is one of the purposes of “Lost and Found” in order to increase the awareness of the public and also taking a solution to solve the missing cases. Before this project starts, reviewing some similar websites is necessary to ensure some of the useful functions can be added and improved to the project and also avoid some non-necessary functions. Interpol, Missing Person, and Missing Kids are some example websites which similar to “Lost and Found”. Later, part of the designs and functionalities of the proposed website are implemented into the project. Firstly, the user can search for the post of the missing people and he or she is also able to upload the missing person’s information on “Lost and Found”. If users have questions, he or she can directly chat with the admin through the live chat system. Some of the basic functionalities such as login, register and user profile are implemented to make the website more systematic. The methods and technologies involved in the project has been developed by using five phases of development that include analysis, design, implementation, testing and documentation. The development of this project is using Visual Studio Code and all the data is store inside phpmyAdmin. The design and the functionalities that implemented in this project is completed. However, The Lost and Found Website still have a lot of improvements and enhancement that could be done in the future.